KORUPSI DALAM PANDANGAN EKONOMI ISLAM - Kencana, Ulya (Program Studi Muamalah Fakultas Syariah dan Hukum, 2017)
Corruption is a phenomenon that gave negative implications for human life, both countries have developed and in developing countries. The issue of corruption to get serious attention from social scientists believed many fields because of corruption as the abuse of power, authority, and embezzlement and bribery significant deviation from the implementation of the value of the trust. Fairness is an important element in the matter of law and law enforcement so no wonder that the Qur'an emphasizes that justice be established though the relatives, even to yourself.